MARKETING COMMUNICATION MODEL TO ACHIEVE MARKETING OBJECTIVES (CASE STUDY OF ORIGAMI PHOTOGRAPHY MEGA MALL MANADO) - Kaloh, Yunita Agmenia; Pangemanan, Sifrid S. (Universitas Sam Ratulangi, 2019)
Abstract: Good quality photo is a common necessity in today's life. Even though mobile phone has been specified with a good camera but the place and photo editing is important to determine whether the photos are good or not. Origami use advertising as their marketing communication tool. The aim of this research is to find out the marketing communication model of Origami Photography Mega Mall Manado in order to achieve their marketing objectives. The sample of this research are management, employee and loyal customer of Origami Photography Mega Mall Manado. The results showed that Marketing Communication Model applied by Origami Photography has significant relationship with the Marketing Objectives. Advertising that is done through in-store displays make people's interest in Origami Photography increase. The impact is seen in Marketing Objectives, sales targets of Origami always achieved every year. Origami Photography need to continue explore unique and interesting designs for their stores. For social media must also be updated more often, maybe they can post photos or update store situation through intagram story. Origami Photography also continues to maintain its loyal customers by keeping their good communication.Â Keywords: marketing communication model, photography, advertising